'Default' generated neonatal regulatory T cells are hypomethylated at conserved non‐coding sequence 2 and promote long‐term cardiac allograft survival. Issue 4 (December 2014) - Cheng, Chao; Wang, Sihua; Ye, Ping; Huang, Xiaofan; Liu, Zheng; Wu, Jie; Sun, Yuan; Xie, Aini; Wang, Guohua; Xia, Jiahong
Summary Regulatory T (Treg) cells play an important role in the maintenance of immune self‐tolerance and homeostasis. We previously reported that neonatal CD4+ T cells have an intrinsic 'default' mechanism to become Treg (neoTreg) cells in response to T‐cell receptor (TCR) stimulation. However, the underlying mechanisms are unclear and the effects of neoTreg cells on regulating immune responses remain unknown. Due to their involvement in Foxp3 regulation, we examined the role of DNA methyltransferase 1 (DNMT1) and DNMT3b during the induction of neoTreg cells in the Foxp3gfp mice. The function of neoTreg cells was assessed in an acute allograft rejection model established in RAG2−/− mice with allograft cardiac transplantation and transferred with syngeneic CD4+ effector T cells. Following ex vivo TCR stimulation, the DNMT activity was increased threefold in adult CD4+ T cells, but not significantly increased in neonatal cells. However, adoptively transferred neoTreg cells significantly prolonged cardiac allograft survival (mean survival time 47 days, P < 0·001) and maintained Foxp3 expression similar to natural Treg cells. The neoTreg cells were hypomethylated at the conserved non‐coding DNA sequence 2 locus of Foxp3 compared with adult Treg cells. The DNMT antagonist 5‐aza‐2′‐deoxycytidine (5‐Aza) induced increased Foxp3 expression in mature CD4+ T cells. 5‐Aza‐inducible Treg cells combined with continuous 5‐Aza treatment prolonged graft survival. These results indicate that the 'default' pathway of neoTreg cell differentiation is associated with reduced DNMT1 and DNMT3b response to TCR stimulus. The neoTreg cells may be a strategy to alleviate acute allograft rejection.